THE IMPORTANCE OF DEVELOPING READING ACTIVITIES IN PRIMARY EDUCATION - Karimova Jahona Uktamjon kizi (Web of Journals Publishing, 2025)
The article highlights the immense importance of fostering interest in reading books, which plays a crucial role in enhancing the spiritual and intellectual potential, consciousness, and worldview of our people, especially the younger generation. It emphasizes the significance of cultivating a well-rounded individual who lives with love and loyalty for their motherland and people.
Keywords: Book, reading, literary book, reader, systematic reading, spiritual thinking, book selection.